ElasticSearch 5.x cookbook : over 170 advanced recipes to search, analyze, deploy, manage, and monitor data effectively with ElasticSearch 5.x /: over 170 advanced recipes to search, analyze, deploy, manage, and monitor data effectively with ElasticSearch 5.x. (2017) - Paro, Alberto
No abstract available